Edukasi Pengelolaan Limbah Rumah Tangga - Willia Novita Eka Rini; Marta Butar Butar; Oka Lesmana (Jurnal Salam Sehat Masyarakat (JSSM), 2022)
Plastic waste is one type of waste whose existence is increasing every day, almost all packaging often uses plastic. As a polymer material, plastic has several advantages such as practicality, airtightness, compactness and elasticity (stretchability). But on the other hand, plastic also has a drawback, namely the amount of waste that accumulates every day because it is difficult to decompose which takes a long time. To solve this problem, it is necessary to find a way to recycle plastic into an economically viable commodity. Alam Barajo sub-district is located in Jambi province which is not far from the center of the crowd because the villages are close to the causeway near the terminal. This area has the potential to develop creative industries. The strategic location and the promised business opportunities are the keys to developing the creative economy. The problem faced by the community, especially in the Alam Barajo District, is the amount of plastic waste, one of which is crackle plastic. Every time you buy food, goods, clothes, etc., they are always wrapped in plastic, which ends up just being thrown away. The targets are members of the Qur'an Friends in the Alam Barajo District training. The method used in the activity of processing crackle plastic waste into plastic flowers. From this activity there was an increase in knowledge of crackle plastic waste processing obtained from the pre-test and post-test with the results of 118 to 151 participants who already knew about the processing of crackle plastic waste and could practice it properly and correctly.